The criteria and factors of effectiveness of innovative development model of Ukrainian economy - Zianko, V. V.; Hrabovetskyi, B. Ye. (Visnyk of Vinnytsia Politechnical Institute, 2010)
The necessity of forming of economy’s innovative development model, directed towards the increasing of entrepreneurs’ demand on scientific and technical development was substantiated; the criteria of its effectiveness were defined; two economic and statistic models defining the influence of key financial factors upon innovative development were elaborated.